2013
DOI: 10.1007/s13202-013-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-salinity flooding in a selected carbonate reservoir: experimental approach

Abstract: Low-salinity waterflooding has been used to improve oil recovery for many decades. Several theories regarding the mechanism of low-salinity flooding have been discussed in the literature including interfacial tension reduction, wettability alteration, change in pH value, emulsion formation, and clay migration. This work presents the results of flooding tests on selected carbonate core samples taken from Bu Hasa field in Abu Dhabi using sea water and two field injection waters, Um-Eradhuma (UER) at 197,357 ppm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(82 citation statements)
references
References 20 publications
6
74
0
2
Order By: Relevance
“…SO 4 2− concentration of about 50 times dilution of SSW, gave the highest recovery [10]. However, in this work diluted SO 4 1:10 gave higher recovery than that for SO 4 1:50.…”
Section: Ion Tracking From Secondary Flooding By Ls Brinesmentioning
confidence: 48%
See 1 more Smart Citation
“…SO 4 2− concentration of about 50 times dilution of SSW, gave the highest recovery [10]. However, in this work diluted SO 4 1:10 gave higher recovery than that for SO 4 1:50.…”
Section: Ion Tracking From Secondary Flooding By Ls Brinesmentioning
confidence: 48%
“…Mole Fraction i-C 5 1.79 × 10 −5 n-C 5 0.000117 C 6 0.002371 C 7 0.013287 C 8 0.039608 C 9 0.062886 C 10 0.881712…”
Section: Componentsmentioning
confidence: 99%
“…So, relative amount of divalent ions was reported to be an important parameter in oil recovery from smart water injection. Al-Attar et al (2013) conducted core flooding tests on carbonate plugs from Bu Hasa field. They injected sea water and field produced water to examine the effect of brine composition and salinity on oil/brine/rock system.…”
Section: Introductionmentioning
confidence: 99%
“…Shehata et al (2015) concluded that existence of divalent ions in the connate water is the more effective compared to monovalent in the sandstones cores (Shehata and Nasr El-Din 2015). In addition, the effects of cations have studied in some studies (Rashid et al 2015;Al-Attar et al 2013;Romanuka et al 2012;Austad et al 2011).…”
Section: Introductionmentioning
confidence: 99%